The Legality Of Miras (Khamr) in Al-Quran Persfective (Comparative Study of The Tafsir Al-Maraghy, Al-Misbah, and Al-Qurthubi) - Muhammad Roni; Ismail Fahmi Arrauf Nasution (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
The discourse on the legality of alcohol in Indonesia has become a hot topic of controversy among various community. The supporters claim that the legality of alcohol is part of local wisdom so it deserves to be legalized. Meanwhile, the majority of Indonesian muslims have rejected this policy with various approaches. This turmoil is interesting to study in order to ground the Qur’an which has long forbidden khamar to be traded. This study used a phenomenological method which is based on the interpretation of the Qur'an, especially the thematic comparisons by the Tafsir Al-Maraghy, Al-Misbah, and Al-Qurthubi. There were three concluding phases of this study; First, the process of forbidding khamar in the Qur'an has certain phases and levels before it is totally prohibited. Second, the most dominant advantage of khamar is only in terms of trading, while the rest has more disadvantages. Third, khamr still applies to emergencies such as medical needs, alchemy, medicine and perfumes. In essence, the legality of alcohol which is to be consumed (drunkenness) is forbidden in Islam.